Supply Chain Analysis of Fruits and Vegetables Produce of the Indigenous People (IP) Farmers in Marilog District, Davao City - Tautho, Dana Gabrielle B.; Tautho, Marie Antonette Paña; Tautho, Diego B. (East Asian Journal of Multidisciplinary Research, 2024)
This study explores the farming and marketing challenges faced by the Matigsalug farmers in Marilog District, Davao City, over the past decade. Utilizing focus group discussions (FGDs) and in-depth interviews (IDIs), it captures the lived experiences of the farmers. The study identifies three key themes: Farming Status, Crop Management, and Marketing Approach. These themes underscore the ongoing challenges in sustainable agriculture and access to markets, while also proposing strategic interventions. The findings are aligned with recent efforts to meet the UN Sustainable Development Goals (SDG), particularly Zero Hunger, and emphasize the importance of policies that enhance agricultural inclusivity. The study contributes to the discourse on supporting Indigenous People (IP) farmers and informs contemporary urban, rural, and regional development planning initiatives.